2006
DOI: 10.1038/sj.bjc.6603326
|View full text |Cite
|
Sign up to set email alerts
|

Health state utilities for metastatic breast cancer

Abstract: The aim of the study was to obtain United Kingdom-based societal preferences for distinct stages of metastatic breast cancer (MBC) and six common toxicities. Health states were developed based on literature review, iterative cycles of interviews and a focus group with clinical experts. They described the burden of progressive, responding and stable disease on treatment; and also febrile neutropenia, stomatitis; diarrhoea/vomiting; fatigue; hand-foot syndrome (grade 3/4 toxicities) and hair loss. One hundred me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
243
5
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(257 citation statements)
references
References 19 publications
6
243
5
3
Order By: Relevance
“…Additionally, costeffectiveness of bevacizumab in metastatic breast cancer has been evaluated [10][11][12]21], with marginal cost effectiveness of $232,720.72 reported by Refaat et al [10]. Although not approved in age-related macular degeneration, bevacizumab is considered an acceptable alternative to ranibizumab based on a randomized trial [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, costeffectiveness of bevacizumab in metastatic breast cancer has been evaluated [10][11][12]21], with marginal cost effectiveness of $232,720.72 reported by Refaat et al [10]. Although not approved in age-related macular degeneration, bevacizumab is considered an acceptable alternative to ranibizumab based on a randomized trial [26].…”
Section: Discussionmentioning
confidence: 99%
“…The dominant theme to emerge from cost-effectiveness studies is that with the exception of the non-lethal condition of age-related macular degeneration for which very small dosages of drug are required, bevacizumab will not be cost-effective in the management of solid tumor malignancies due to the current high cost of the drug, relatively limited impact on duration of survival, and healthcare expenditures required to manage anti-VEGF-specific toxicology [10][11][12]15,16,18,20,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kulikov et al (2015), based on a global model, which formed the basis of further analysis of effectiveness [3]. In this study we developed an adapted model using the Kaplan-Meier method for calculation of effectiveness criteria over three years [29,31,32,34]. The criteria of effectiveness / utility were determined as a result.…”
Section: Analysis Of Effectivenessmentioning
confidence: 99%
“…Because no utility score, which was applicable to this study, in Japanese women with MBC was found, utilities for health states were obtained from literatures 20) . Health state utility values from United Kingdom general public for health states related to stable, responding and progressive MBC were reported using the mixed model based on standard gamble in 2006.…”
Section: Utilitiesmentioning
confidence: 99%